The impact of subsidy program toward paddy productivity / Mohd Fikry Harun - Harun, Mohd Fikry (Faculty of Plantation Management and Agrotechnology, 2017)
Rice has been a staple food of the Malaysian community and the paddy/rice industry is considered as a strategic industry and always get special treatment from the government. Thisstudy attempts to evaluate the effectiveness of the subsidy program to the farmer. The purpose of this research is to identify the effectiveness of current progress toward paddy productivity. The study was done at the paddy smallholder’s area in Merlimau, Malacca and the population size was 180 farmers , therefore the expected sample size were123 farmers. In obtained primary result, the questionnaire weredistributed to 123 respondent, using the random sampling methodand data analysis was analysed by used descriptive analysis, SPSS and Microsoft Excel. Apart from that, the research also examine and the pattern of input supply of rice in Malaysia rice production to improve production yield. The regression result from this study indicateand that changes in the schedule distribution and inspection is the key determinant of theuse in paddy productivity. However, the input supply does not influence the paddy productivity. Meanwhile, input supplies are not able to influence the effectiveness of the productivity of rice caused by factors subsidy content provided is insufficient inquantity specified. Inconclusion the dominant factor that successfully influence the paddy productivity is the schedule distribution and follow by inspection. The recommendation is action must be taken by the(Board of Plantation Industries Association)(FOA) is a must provide an adequate amount of input supply to farmers and by the procedures that are in limit. The rate must also be distributed on the basis of pre-defined and based on land area farmers to avoid leakages in the distribution process. In addition, in terms of monitoring should also be regularly carried out to ensure farmers can guidance and advice of agricultural officers.